THE IMPLEMENTATION OF CREDIT RISK SCORECARD MODEL TO IMPROVE THE ASSESSMENT OF CREDITWORTHINESS IN A PEER-TO-PEER LENDING COMPANY - Taufik Faturohman; Raden Aswin Rahadi; Rendy Franata (International Journal of Accounting, Finance and Business, 2018)
The most common problem in the financial service industry is the risk problem. Oneof the most crucial risk problems is default risk. Nowadays, the users of peer-to-peer (P2P)lending companies are growing rapidly; however, the companies have not prepared an adequatesystem to assess them. Furthermore, the company must have a different assessment model foreach other. One assessment model which is currently used by the companies is 5C CreditAnalysis. Through this research, the author constructs a credit scoring model which is based onthe historical data to be implemented in a P2P lending company. The data used come from aP2P lending company in Bandung, Indonesia. The author chooses the Credit Risk ScorecardModel to predict the customer’s creditworthiness assessment. The result indicates the modelconstructed is better than 5C Credit Analysis. It is shown by the Pearson correlation value, wherethe model generates higher significant value than 5C's Credit Analysis. Moreover, the model istested using cross-validation test and resulted the optimum is occurred in the proper cut-off valueof 0.235 with the accuracy rate, sensitivity rate, and misclassification rate, respectively as for69.84%, 77.27%, and 28.24%. Moreover, the result is almost similar to the previous study whichis used as the literature in this research